Expenses and Profits of Limited Price Variety Stores in 1947 (Book). - Smith, Frank P.; Dickman, A. B. (The Accounting Review, 1949)
Abstract Reviews the book "Expenses and Profits of Limited Price Variety Stores in 1947," by Milton P. Brown.